The design and implementation of a motor drive for foot rehabilitation. (November 2016) - Ho, Tze-Yee; Chen, Yuan-Joan; Chen, Po-Hung
Highlights: An electric foot rehabilitation machine based on an ARM microcontroller is designed and implemented. The hardware structure of the foot rehabilitation device includes an ARM microcontroller, motor drive, BLDC motor. The ARM microcontroller generates three phase pulse width modulation signals to the motor drive to control the BLDC motor in such a way to bring the foot to step forward or backward. The PI control is employed to the speed controlled motor drive system. Abstract: The aim of this paper is to present the design and implementation of an electric foot rehabilitation machine that uses an advanced RISC (reduced instruction set computer) machine (ARM) microcontroller based brushless dc (BLDC) motor drive. The function of the electric foot rehabilitation machine is to help patients who need physical therapy for a foot. The goal is for patients to have increased muscle strength after rehabilitation. The system hardware and software are designed and programmed. The proportion, integration and derivation (PID) control algorithm is employed to the motor drive for the speed and torque control. A user interface is also developed and implemented to provide a user-friendly experience. Finally, a prototype of the foot rehabilitation machine is built and tested. The experimental results demonstrate the feasibility and integrity of the complete system. Graphical abstract: